Global positioning system data analysis: Velocity ranges and a new definition of sprinting for field sport athletes - Dwyer, D. B.; Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2012)
Global positioning system (GPS) technology has improved the speed, accuracy, and ease of time-motion analyses of field sport athletes. The large volume of numerical data generated by GPS technology is usually summarized by reporting the distance traveled and time spent in various locomotor categories (e.g., walking, jogging, and running). There are a variety of definitions used in the literature to represent these categories, which makes it nearly impossible to compare findings among studies. The purpose of this work was to propose standard definitions (velocity ranges) that were determined by an objective analysis of time-motion data. In addition, we discuss the limitations of the existing definition of a sprint and present a new definition of sprinting for field sport athletes. Twenty-five GPS data files collected from 5 different sports (men's and women's field hockey, men's and women's soccer, and Australian Rules Football) were analyzed to identify the average velocity distribution. A curve fitting process was then used to determine the optimal placement of 4 Gaussian curves representing the typical locomotor categories. Based on the findings of these analyses, we make recommendations about sport-specific velocity ranges to be used in future time-motion studies of field sport athletes. We also suggest that a sprint be defined as any movement that reaches or exceeds the sprint threshold velocity for at least 1 second and any movement with an acceleration that occurs within the highest 5% of accelerations found in the corresponding velocity range. From a practical perspective, these analyses provide conditioning coaches with information on the high-intensity sprinting demands of field sport athletes, while also providing a novel method of capturing maximal effort, short-duration sprints.